INFLUENCE OF LOCAL VIBROSTIMULATION ON FOCUS PERSISTENCE - Ciematnieks, Uģis; Gasjūne, Rolanda; Saulīte, Sergejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Nowadays computers, data input and processing is vital part of many companies, and this job is carried out mostly by humans. Employees have to focus all the day for not to allow errors. In many companies there can be a several breaks for rest. Local vibrostimulation is a vibration method, which can offer stimulating, tonic effect on central nervous system, therefore increasing human physical abilities. Aim of research: Comparison of 30-45 year old, physically active and inactive women under the influence of local vibrostimulation. Participants carried out digital focus test for one week long, during a second week they executed this test again after a local vibrostimulation session. After processing average results we observed significant increasement (0.956 before vibrostimulation and 1.381sec after vibrostimulation) in focus persistence test, which makes us believe that local vibrostimulation of upper back muscles can lead to focus increasement of office workers.